Modeling Terrorism Risk to the Air Transportation System An Independent Assessment of TSA's Risk Management Analysis Tool and Associated Methods - Morral, Andrew R. (RAND Corporation, 2012)
RAND evaluated a terrorism risk modeling tool developed by the Transportation Security Administration and Boeing to help guide program planning for aviation security. This tool-the Risk Management Analysis Tool, or RMAT-is used by TSA to estimate the terrorism risk-reduction benefits attributable to new and existing security programs, technologies, and procedures.